Effect of Different Plant Growth Regulators on Growth and Yield of Tomato (Lycopersicon esculentum) - Poudel, A.; Duwadi, A.; Acharya, A.; Gyawali, P.; Bhatt, R.; Gautam, S.; Srivastava, A. (Journal of the Institute of Agriculture and Animal Science, 2020)
A field experiment was conducted at the research field of the Department of Horticulture, Agriculture and Forestry University, Rampur, Chitwan, to study the effects of plant growth regulators in an open-pollinated variety of tomato, Lycopersicon esculentum var. BL selection 410 in four replicates. The trial was laid out in Randomized Block Design with six treatments; Indole-3-butyric acid (IBA) at 25 ppm and 50 ppm, Gibberellic acid (GA3) at 25 ppm, and 50 ppm, and a cocktail of IBA and GA3 at 25 ppm each. Higher plant height was recorded in GA3 at 50 ppm. Similarly, maximum yield (39.6 MT/ha), individual fruit weight (19.1 gm), number of fruits per plant (55.5), and number of flower clusters per plant (17.65) was recorded with the combined application of IBA and GA3 at 25 ppm.